Nitritation via heat shock using immobilized active sludge aggregates. Issue 48 (20th October 2016) - Chen, Guanghui; Li, Jun; Wei, Jia; Zeng, Jinping; Zhang, Yanzhuo; Bian, Wei; Deng, Hailiang
Abstract: The nitritation process is considered to be one of the most energy-saving and efficient methods for treating polluted water. In this study, active sludge was immobilized with waterborne polyurethane (WPU), and a heat-shock method was employed to treat the immobilized aggregates. When environmental factors that adversely affect nitritation (pH, dissolved oxygen, temperature, etc.) were controlled, steady nitrite nitrogen accumulation was also successfully achieved. We investigated the effect of temperature and timing of the heat-shock method on the activity of ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) using polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE). Subsequently, temperatures of 60 and 70°C were selected to evaluate the nitritation stability of the heat-shocked immobilized aggregates, and continuous-flow experiments were conducted. The results of preliminary experiments indicated that NOB can be completely deactivated at temperatures above 60°C after 10 min, whereas AOB continued to exhibit some activity. In addition, the effect of temperature was more significant than the effect of heating time for NOB. The results of the nitritation stability assay indicated that the heat-shocked immobilized aggregates that formed at two temperatures remained in stable nitritation; however, the performance of the AOB was decreased at the highest temperature tested. A high temperature and long duration were required for stable nitritation. In the continuous-flow experiments, we discovered that nitrate nitrogen accumulation occurred after 65 d of operation. Therefore, the immobilized aggregates were heat shocked again, and nitrite nitrogen accumulation recurred in the reactor (results not shown). Heat shock is an effective method for stabilizing the nitritation of immobilized nitrifying sludge; this method also provides new ideas for a nitritation-based nitrogen removal process. Key innovations are: (1) a new nitration method based on heat shock has been proposed to generate steady nitritation using immobilized bacterial aggregates; (2) polymerase chain reaction (PCR) has been applied to analyze variations in the AOB and NOB populations of immobilized aggregates before and after heat shock; (3) optimal heat-shock conditions (including duration and temperature) have been identified.